Application of the E-module combined with the Guided Inquiry Learning Model to Increase Student Motivation and Learning Outcomes on the Structure and Function of Plant Tissues - Arina Dini; Hafnati Rahmatan; Muhibbudin; Cut Nurmaliah; Safrida (Jurnal Penelitian Pendidikan IPA, 2023)
The low learning motivation of students is a classic problem that often occurs in the teaching and learning process and has an impact on learning outcomes. One way that can be used by teachers in solving motivational problems and student learning outcomes is by applying innovative learning media such as e-modules combined with guided inquiry learning models. This study aims to determine differences in learning motivation, differences in increasing learning outcomes and the relationship between motivation and student learning outcomes through the application of e-modules combined with guided inquiry on the material structure and function of plant tissue. This research is quantitative with experimental research methods and research design Pre-test Post-test Control Group Design. The population in this study were 214 students from class XI IPA at SMAN 1 Darul Imarah and SMAN 1 Peukan Bada Aceh Besar. The research sample consisted of 121 students who were divided into two classes, namely the control class and the experimental class. The parameters of this study are the motivation and learning outcomes of students. The instrument for measuring motivation used 36 items of the ARCS motivational questionnaire, while learning outcomes were measured using 40 multiple choice tests. The increase in learning outcomes is calculated by the N-gain formula. Data analysis to see differences in motivation and differences in increasing learning outcomes used Mann Whitney test analysis, while analysis of the relationship between motivation and learning outcomes used Pearson's Product Moment correlation analysis. The results showed that there were differences in students' learning motivation (p <0.05), there were significant differences in increasing learning outcomes (p <0.05), there was a significant relationship between motivation and student learning outcomes. The conclusion of this study is that there are differences in motivation and differences in the increase in student learning outcomes after applying learning using e-modules combined with guided inquiry. Â